UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MATERI ZAKAT DENGAN MENGGUNAKAN METODE TEAM QUIZ PADA KELAS X MIA 2 SMA NEGERI 1 KEPENUHAN - Makmur Makmur (STKIP ROKANIA, 2021)
This study discusses efforts to improve fiqh learning outcomes, the subject matter of zakat in class X MIA 2 SMA Negeri 1 Kecepatan for the 2019/2020 school year. This research is motivated by the phenomenon of low learning outcomes which are marked by the lack of students who are able to exceed the KKM score. In this study, the use of the team quiz method in learning fiqh, the subject matter of zakat, is offered. The formulation of the problem put forward is